Analysis of the efficiency indicators of cargo delivery distribution system - Bakulich, Olena; Musatenko, Olena; Samoylenko, Evgeniy (Technology audit and production reserves, 2016)
This article is highlighted results of the studying the main characteristics of the cargo delivery distribution system and studied regularities of deliveries by road transport, which was the aim of the article. The methods of field observations to collect statistical information and statistical analysis methods for establishing and verifying the adequacy of regression were used in the article. Literature review shows that the most effective method for studying topological structures of cargo delivery is simulation. Patterns of changes in key parameters of the distribution system were studied for its reliable implementation. There are: time, cost and reliable of cargo transportation. The dependences and characteristics of change the basic characteristics of the distribution system create the basis for further adequate simulation modeling of goods delivery process in distribution systems, which will examine the impact of different topological organizational structures of distribution and inventory management strategies on the efficiency of delivery. The results of this simulation, in the opinion of the authors, will enable to determine the optimal volume of goods delivery in concrete terms of delivery system and its effective topological structure for the appropriate transport technologies.